Mulheres e educação: gênero, raça e identidades - Carneiro, Aparecida Suelaine (2015)
This study aims to analyze the participation of women in education and its connection with the actions taken by the Brazilian feminist movement. The Brazilian education experiences the greater participation and better performance of women, however racial belonging, gender and sexuality are markers that result in inequalities observed in the persistence of disparities in education. Oral history is the methodology used to record the voices of six students of vocational high school of the state system school. Their life stories contains information on the understanding of being a woman in Brazilian society, in education, in the professional market, the determinants for the choice of technical courses as well as for understanding the sexual segregation residence in technical courses. The reports showed evidence of the presence of constituent processes of socialization of gender roles, hierarchies in professional careers, as well as the tensions that mark the entry of women in predominantly male courses. It is also noticed the lack of actions and achievements of the feminist movement that contributed to transformations in the lives of Brazilian women in recent decades, and little commitment to a political action in favor of women. We tried to explain the challenge of education for effective mechanisms to expand the future possibilities for women as well as for the construction of pedagogical practices committed to equality, freedom and fairness.